(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Pediatric urolithiasis (UL) should not be underestimated, because it is associated with significant morbidity, particularly because stones tend to recur. Objective:To study the demographic characteristics, clinical manifestations, metabolic disorders and some risk factors for stone formation in a group of Iraqi children. Methods: A total of 96 children with UL comprised 66 males and 33 females with an age range 0.1-14 years were studied for the period from 1st of January 2009 to the end of December 2011. Results:Positive family history was present in 29 patients (30.2%); all of them had metabolic disorder. Recurrence rate of stone was recorded in 41 (42.7%); of them 28 (68.3%) had metabolic disorder. The commonest clinical presentation was urinary tract infection in 40 (41.7%). Urine culture was positive in 57 (59.3%) children predominated by E.Coli in 23 (40.3%). Twenty four hour urine collection were positive for metabolic disorders in 84 patients (87.5%) and mainly hypercalciurea in 53 (63 %), hyperoxalurea in 31 (36.9%), hyperuricosurea in 23 (27.3%), and cystinurea in 15 (17.8%). Staghom calculi were detected in 6 patients (6.2%), all are associated with infection. Chemical analysis show calcium salt as major component in 22 out of 33 stones (66.6%). Predisposing risk factors for stone formation was established in 91 patients (94.8%) while no etiology could be found in 5 (5.2%). Metabolic disorders were the major risk for stone formation in 54 (56.3%), infection in 21(21.8%) and renal anomalies in 16 (16.7%). Conclusion:Metabolic disorders were found to be the major predisposing factors to stone formation among this group of Iraqi children. Early presentation, family history of stone disease, high recurrence rate of UL, bilateral and multiple stones are all indicators for metabolic disorders which mandate complete metabolic evaluation in pediatric stone formers. Keywords: Urolithiasis, stones, metabolic, children